2017
DOI: 10.3390/ijms18040170
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of MCT1, MCT4 and CD147 Genes in Peripheral Blood Cells of Breast Cancer Patients and Their Potential Use as Diagnostic and Prognostic Markers

Abstract: Background: Patients with breast cancer—the deadliest cancer among women—are at constant risk of developing metastasis. Oxidative stress and hypoxia are common feature of tumor cells that can proliferate even in a resultant metabolic acidosis. Despite the low extracellular pH, intracellular pH of tumor cells remains relatively normal, or even more alkaline due to the action of a membrane protein family known as monocarboxylate transporters (MCTs). The objective of this study was to verify the diagnostic and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 37 publications
(49 reference statements)
2
14
0
Order By: Relevance
“…Although extensive studies can be readily available regarding the MCT1 in cancers of different types; it has been little described in esophageal cancer with the exception of two recent related reports [17,18]: one about MCT1 expression in Barrett's esophagus and adenocarcinoma, the other ESCC. Analysis from previous investigations concerning MCT1 in cancers, regardless of different types [19][20][21][22], revealed that MCT1 prevailed or predominantly over-expressed in cancerous tissues as compared with normal controls and up-regulated MCT1 was found to be linked with poor outcome as well as tumor metastases, which was fully in agreement with our observations in ESCC of our own case. What's congruent with our description with regard to MCT1 is that, in a recent study [18] by Chen X and colleagues, MCT1 was exhibited to be an independent prognostic factor in ESCC.…”
Section: Discussionsupporting
confidence: 92%
“…Although extensive studies can be readily available regarding the MCT1 in cancers of different types; it has been little described in esophageal cancer with the exception of two recent related reports [17,18]: one about MCT1 expression in Barrett's esophagus and adenocarcinoma, the other ESCC. Analysis from previous investigations concerning MCT1 in cancers, regardless of different types [19][20][21][22], revealed that MCT1 prevailed or predominantly over-expressed in cancerous tissues as compared with normal controls and up-regulated MCT1 was found to be linked with poor outcome as well as tumor metastases, which was fully in agreement with our observations in ESCC of our own case. What's congruent with our description with regard to MCT1 is that, in a recent study [18] by Chen X and colleagues, MCT1 was exhibited to be an independent prognostic factor in ESCC.…”
Section: Discussionsupporting
confidence: 92%
“…Although extensive studies can be readily available regarding the MCT1 in cancers of different types; it has been little described in esophageal cancer with the exception of two recent related reports [17,18]: one about MCT1 expression in Barrett's esophagus and adenocarcinoma, the other ESCC. Analysis from previous investigations concerning MCT1 in cancers, regardless of different types [19][20][21][22], revealed that MCT1 prevailed or predominantly over-expressed in cancerous tissues as compared with normal controls and up-regulated MCT1 was found to be linked with poor outcome as well as tumor metastases, which was fully in agreement with our observations in ESCC of our own case. What's congruent with our description with regard to MCT1 is that, in a recent study [18] by Chen X and colleagues, MCT1 was exhibited to be an independent prognostic factor in ESCC.…”
Section: Discussionsupporting
confidence: 92%
“…Monocarboxylic acid transporter 4 (SLC16A3/MCT4) is one of the membrane protein stubs in cells that is structurally able to output lactic and pyruvic acids and affect the acidity of the tumor microenvironments. [15][16][17] High expression of MCT4 has been reported to be a biomarker in various types of tumors, [18][19][20][21][22][23][24] which makes it an appealing therapeutic target in cancers. The blockade of MCT4 expression has been shown to represent a novel treatment target in glioblastoma, large B-cell lymphoma, and multiple myeloma.…”
Section: Introductionmentioning
confidence: 99%